Nothing new in Europe? : Israelis look at antisemitism today - Haviv-Horiner, Anita 1960- (Berghahn Books, 2022)
"Today, more than 75 years after the Holocaust and World War II, antisemitism remains a poisonous force in European culture and politics, whether cloaked in the garb of reactionary nationalism or manifested in outright physical violence. Nothing New in Europe? provides a sobering look at the persistence of European antisemitism today through fifteen interviews with Jewish Israelis living in Germany, Poland, France, and other countries, supplemented with in-depth scholarly essays. The interviewees draw upon their lived experiences to reflect on anti-Jewish rhetoric, the role of Israel, and the relationship between antisemitism and the persecution of other minorities"--